The structure and evolution of deepwater basins in the distal margin of the northern South China Sea and their implications for the formation of the continental margin. (April 2018) - Yang, Linlong; Ren, Jianye; McIntosh, Kirk; Pang, Xiong; Lei, Chao; Zhao, Yanghui
Abstract: Although it is generally accepted that the South China Sea margin can be classified as a magma-poor rifted margin, little is known about the structural style of the distal margin and how the distal deep basins evolved. Observations and data from the Northern South China Sea margin suggest that the deepwater basins (distal margin domain) are commonly underlain by a highly extended continental crust, and detachment fault systems have been interpreted in places. We have interpreted a large seismic data set covering deepwater basins in the Northern South China Sea. The interpreted Moho on reflection seismic profiles indicates that the crustal thickness varies along sections perpendicular to the coast, which is the first-order criterion to divide the whole margin into a proximal domain, necking zone and distal domain. Furthermore, the underlying extremely stretched crust (<10 km) is always accompanied by obvious fault reflections with shallow dips and large-scale sedimentary basins. One major achievement of our study is the relationships between these detachment faults and rifted basins. By integrating well data and published bathymetry data, we built the tectono-stratigraphy framework and mapped the distribution of these detachment faults. From the Qiongdongnan basin, Heshan sag, and Baiyun sag, a complex polyphase evolution can be identified. Generally, the overall evolution of these supradetachment basins can be divided into three phases. Initial rifting, which is characterized by distributed, limited-offset faulting with grabens or half-grabens bounded by steeply dipping faults. Later, focused deformation occurred in the form of detachment faulting with large horizontal displacement and large subsidence. During this phase, the intense rotation of the detachment faults is responsible for the intra-rifting unconformities and tilted block (Heshan Sag). Finally, the occurrence of sag sequences in the basins suggests likely deformation migration oceanward, as described in recent numerical modeling studies. Highlights: The detachment faults, tilted fault blocks and thinned continental crust are interpreted based on the 2D and 3D seismic data. Analysis of the tectono-stratigraphic framework in the distal margin reveal the development of the supra-detachment basin. The northern South China Sea is divided into the proximal domain; the necking zone; the distal margin.